Linear discriminant analysis reveals differences in root architecture in wheat seedlings by nitrogen uptake efficiency - Kenobi, Kim; Atkinson, Jonathan A.; Wells, Darren M.; Gaju, Oorbessy; deSilva, Jayalath G.; Foulkes, M. John; Dryden, Ian L.; Wood, Andrew T.A.; Bennett, Malcolm J. (Oxford University Press, 2017)
Root architecture impacts water and nutrient uptake efficiency. Identifying exactly which root architectural properties influence these agronomic traits can prove challenging. In this paper approximately 300 wheat plants were divided into four groups using two binary classifications, high vs. low nitrogen uptake efficiency (NUpE), and high vs. low nitrate in medium. The root system architecture for each wheat plant was captured using 16 quantitative variables. The multivariate analysis tool, linear discriminant analysis, was used to construct composite variables, each a linear combination of the original variables, such that the score of the wheat plants on the new variables showed the maximum between-group variability. The results show that the distribution of root system architecture traits differ between low and high NUpE wheat plants and, less strongly, between low NUpE wheat plants grown on low vs. high nitrate media.